Analisis Distribusi Umur Pengelola Usaha Pertanian Perorangan (UTP) di Provinsi Nusa Tenggara Timur - Antonius Andri Geong (Badan Pusat Statistik Provinsi NTT, 2025)
The agricultural sector plays a crucial role in Indonesia’s economy, yet farmer regeneration remains a significant challenge. This study examines the age distribution of Individual Agricultural Holding (UTP-Usaha Pertanian Perorangan) in Nusa Tenggara Timur (NTT) using data from the 2023 Census of Agricultural. The findings indicate that most UTP holders are over 35 years old, with the highest proportion in the 45-54 age group. Meanwhile, younger managers (<35 years old) constitute only a small proportion of the total, highlighting concerns regarding the sustainability of the agricultural workforce. The study employs descriptive analysis and statistical inference using Welch ANOVA. The results show a left-skewed age distribution (skewness=-0.47), indicating an aging agricultural workforce. The Welch ANOVA test confirms significant differences in the number of UTP holders across age groups, and the post hoc Games-Howell test further highlights the underrepresentation of younger generations in agriculture workforce. The findings emphasize the urgent need for strategic policies to attract young farmers, including improved access to capital and land, the adoption of modern agricultural technologies, and competitive economic incentives. Future research should explore multivariate regression models to identify key factors influencing farmer regeneration in NTT and develop targeted